Strengthening the Role of Christian Education in Families as an Effort to Address Human Trafficking in the City of Jayapura Papua Province - Rendy Christian Lande; Demsy Jura (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The article, titled "Strengthening the Role of Christian Education in Families as an Effort to Address Human Trafficking in the City of Jayapura, Papua Province," is a study on efforts to address human trafficking crimes through the role of Christian education within families. The intended strengthening of roles involves all elements within the family itself. The article highlights the expectation that, through this study, the community in the city of Jayapura, Papua Province, can gain a true understanding of human trafficking crimes and comprehend how the role of Christian education in the family can contribute to reducing the crime rate. The research approach employed in writing this article is qualitative, based on literature review.